1985
DOI: 10.1113/jphysiol.1985.sp015589
|View full text |Cite
|
Sign up to set email alerts
|

Shortening velocity extrapolated to zero load and unloaded shortening velocity of whole rat skeletal muscle.

Abstract: 2. The Vmai was 3-2+0-1 (mean+s.E. of mean, n = 10) fibre lengths/s while the V0 determined for the same muscles was 5-0 + 0-1 fibre lengths/s. The ratio of V0/ Vmax was 1P6+041.3. Soleus muscles of the rat are heterogeneous with respect to the intrinsic shortening velocities of their fibres. The results suggest that VI is a measure of the unloaded shortening velocity of the fastest fibres whereas Vmax is a function of the force-velocity characteristics of all the fibres within a skeletal muscle preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 15 publications
2
61
1
Order By: Relevance
“…Akster, Granzier & ter Keurs (1985) found a value of 160 kN/m2 in perch red head muscle. Claflin & Faulkner (1985) and Ranatunga (1984) found values between 150 and 160 kN/m2 in rat soleus at 20 0C (which also contains fast fibres).…”
Section: Activation Of Red Muscle Bundlesmentioning
confidence: 96%
See 1 more Smart Citation
“…Akster, Granzier & ter Keurs (1985) found a value of 160 kN/m2 in perch red head muscle. Claflin & Faulkner (1985) and Ranatunga (1984) found values between 150 and 160 kN/m2 in rat soleus at 20 0C (which also contains fast fibres).…”
Section: Activation Of Red Muscle Bundlesmentioning
confidence: 96%
“…The parameters for the hyperbola were iteratively chosen so as to minimize the squared errors in velocity between the chosen hyperbola and the data (as in Claflin & Faulkner, 1985). Because Because passive tension did not appear to be temperature dependent, the lowest load utilized on a given bundle was approximately the same at both 10 and 20 'C.…”
Section: Measurement Of Vmax Of Red Bundlesmentioning
confidence: 99%
“…Force measurements (in Newtons) were normalized to muscle cross-sectional area (cm 2 ). The unloaded shortening velocity (V 0 ) of isolated extraocular muscles was determined with slack tests (Claflin and Faulkner, 1985). Briefly, muscles were stimulated to contract maximally for 350 msec; 250 msec into the stimulation train the muscle was shortened abruptly, causing force to fall to zero.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between in vitro activation and natural recruitment of extraocular muscle fibers also may explain the lack of an in vivo correlate for the impaired V 0 . In heterogeneous muscles, such as the extraocular muscles, V 0 is a measure of the speed of shortening of the fastest muscle fibers present (Claflin and Faulkner, 1985). In the extraocular muscles these fibers should be those expressing the ultrafast extraocular musclespecific myosin isoform, i.e., the orbital singly innervated fibers (OSIF).…”
Section: Functional Deficitsmentioning
confidence: 99%
“…7); it seems that faster HAR played a role in reducing HCV sufficiently, resulting in similar HCV among younger adults while walking faster in comparison to older adults. The previous studies [38][39][40][41][42] found that maximal unloaded shortening velocity in fast-twitch fibers was faster in comparison to slow-twitch fibers and suggested that fast-twitch fibers produced higher force in comparison to slow-twitch fibers in a given time [38][39][40][41]. Also, many studies demonstrated a direct relationship between muscle force and EMG activity [36,[43][44][45][46].…”
Section: Hamstring Activation Rate In Older Adults Was Lower Than Thementioning
confidence: 99%